IoT Circuit Design to Monitor Cold Chain Refrigerators (2019)
Under the concept of the Internet of Things, was designed a PCB to monitor faults in refrigerators or freezers, which use conventional compressors or non-inverters. It should be emphasized that these equipment belong to a cold chain, where it is considered approximately 2000 refrigerators. This solution includes among its main requirements Sigfox wireless communication, to send data or alarms from refrigerators or end nodes to the server in the cloud. One of the attractions to choose SigFox technology is its low cost as a communication service. Other aspects of design are: control the compressor, alert operational failures, measure the temperature inside the freezer, measure power consumption, voltage and current. Another fundamental requirement of the design is to achieve a low cost in its production to be in the margin of the sale of conventional temperature controllers, perhaps not equal, but not be well above the commercial value. With these premises, the hardware architecture is basically composed by a Switched-Mode Power Supply (SMPS), a control unit with a PIC32, 5VDC relays to switch an output of 220V AC, NTC temperature sensor, Power meter IC, battery charger, Sigfox communication module and E-Paper Display. © 2019 IEEE.